2003
DOI: 10.3354/dao055205
|View full text |Cite
|
Sign up to set email alerts
|

Age- and weight-dependent susceptibility of rainbow trout Oncorhynchus mykiss to isolates of infectious haematopoietic necrosis virus (IHNV) of varying virulence

Abstract: The virulence of 5 European and 1 North American isolate of infectious haematopoietic necrosis virus (IHNV) was compared by infecting female sibling rainbow trout ('Isle of Man' strain) of different weights and ages (2, 20 and 50 g). The fish were exposed to 10 4 TCID 50 IHNV per ml of water by immersion, and the mortality was recorded for 28 d. Two new IHNV isolates from Germany were included in the investigation. One was isolated from European eels kept at 23°C (± 2°C) and the other was not detectable by imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 13 publications
2
29
0
1
Order By: Relevance
“…Age-and weight-dependent susceptibility of rainbow trout (Oncorhynchus mykiss) to IHNV has been well documented (20). In the current study, N2G3 presented the best balance between attenuation and protection.…”
Section: Virus Infectivity and Vaccine Potential Of N2g3 Virus In Troutmentioning
confidence: 70%
“…Age-and weight-dependent susceptibility of rainbow trout (Oncorhynchus mykiss) to IHNV has been well documented (20). In the current study, N2G3 presented the best balance between attenuation and protection.…”
Section: Virus Infectivity and Vaccine Potential Of N2g3 Virus In Troutmentioning
confidence: 70%
“…In 1998, an IHNV isolate, DF13/98, was isolated from diseased farmed Anguilla anguilla kept at 23°C in Germany (Bergmann et al 2003). Rainbow trout of various age and weight classes were infected with DF13/98 by immersion and reared for 28 d at 9°C.…”
Section: Other Rhabdoviruses Isolated From Anguilla Anguillamentioning
confidence: 99%
“…The virus appeared to be highly pathogenic for intraperitoneally infected rainbow trout fry (3 mo old) at 13°C, with a cumulative mortality of 89%, but much less pathogenic for 5 mo old rainbow trout fingerlings, with a mortality of only 15%. The pathogenicity of the isolated virus for eel, as well as the origin of the elver contamination, remains unknown.In 1998, an IHNV isolate, DF13/98, was isolated from diseased farmed Anguilla anguilla kept at 23°C in Germany (Bergmann et al 2003). Rainbow trout of various age and weight classes were infected with DF13/98 by immersion and reared for 28 d at 9°C.…”
mentioning
confidence: 99%
“…Numerous studies have demonstrated differential susceptibility between age cohorts of the same host species, normally in the context of aquaculture, whereby early age classes (such as eggs and larvae) can be afflicted by different diseases (or the same diseases at a different prevalence and severity) to those observed in adult life stages (e.g. Kiran et al 2002, Bergmann et al 2003. This concept provides a rationale to consider whether similar phenomena may be apparent in natural (wild) populations of aquatic animals and furthermore, whether differential age of onset for the same disease may occur across geographical regions or temporally.…”
Section: Introductionmentioning
confidence: 99%